(untitled) (Research, Society and Development, 2022)
The present study aims to evaluate the impacts and the degree of satisfaction of the members participating in the Sobre Vida extension project during medical graduation. Methodology: Retrospective, cross-sectional, observational, descriptive study carried out with medical students who participated in the Project and collected through an electronic questionnaire through access in a virtual form for academics who fit the inclusion criteria. Results: The research was carried out with 27 academics who graduated from the survival extension project through a questionnaire. Of the total, 25 responded that they would participate again in the project. In addition, 22 showed to be very satisfied with the contact with basic life support matters in a deeper way. Regarding the level of confidence to provide help, 15 claimed to provide with some confidence. No former member considers himself completely unprepared. Finally, when asked if the project brought benefits to their academic life, all 27 participants answered yes. Conclusion: After collecting and analyzing the data, the project was successful in bringing knowledge to lay people in addition to benefiting all former members as a medical student.